Analysis of fire and hazardous sites (zones) in coal mines and the causes of coal self-ignition - Antoshchenko, Mykola; Tarasov, Vadym; Zakharova, Olha (Technology audit and production reserves, 2019)
Annually, dozens of endogenous fires are recorded in Ukrainian mines. To date, mining and geological factors have not been reliably established that contribute to the development of foci of spontaneous combustion of coal in characteristic places (zones) of the mine field. Thus, the object of research is the process of spontaneous combustion of coal from fire hazardous areas (zones) in coal mines. An analysis of the results of the investigation of endogenous fires shows that the areas of spontaneous combustion can be accumulation of losses of chipped coal in the working and developed space of exploited lavas, and the developed space of stopped faces, the edge parts of the array of the developed seam or protective solid blocks of coal. As well as close underworked and overworked seams, treatment and extended mine workings in and out of zones of influence of geological disturbances, accumulation of coal after its sudden release during a gas-dynamic phenomenon and the cavity of this discharge. Ceteris paribus, the factor of the presence of prolonged contact of mine air with the accumulation of chipped coal is a necessary condition for the occurrence of foci of spontaneous combustion. It is shown that with reciprocal schemes for ventilating excavation sections of gently sloping and inclined-fall formations, all fire sources occurred in zones adjacent to recoil or ventilation workings. At the same time, about 70 % of endogenous fires during the development of steeply falling seams occurred near the recoil mine due to the accumulation of large volumes of coal and the supply of a fresh air stream of air to the lava working space. The research results show that the thickness of the developed formation and the angle of its fall do not directly affect the accumulation of broken coal. They can’t be the main factors determining the foci of endogenous fires, as is customary in normative documents. The obtained results contribute to the improvement of the regulatory framework for the safe development of formations prone to spontaneous combustion, including gas-bearing ones.